2013
DOI: 10.1002/pmic.201200472
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the naringenin-inducible proteome inRhizobium leguminosarumby isobaric tagging and mass spectrometry

Abstract: The rhizobium-legume interaction is a critical cornerstone of crop productivity and environmental sustainability. Its potential improvement relies on elucidation of the complex molecular dialogue between its two partners. In the present study, the proteomic patterns of gnotobiotic cultures of Rhizobium leguminosarum bv. viciae 3841 grown for 6 h in presence or absence of the nod gene-inducing plant flavonoid naringenin (10 μM) were analyzed using the iTRAQ approach. A total of 1334 proteins were identified cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…The prominent feature of this group of bacteria is their molecular dialogue with plant hosts, an interaction that is enabled by the presence of a series of symbiotic genes encoding for the synthesis and export of signals triggering organogenetic and physiological responses in the plant (Spaink et al, 1987; Long, 2001). In recent years, significant progress has been made in resolving the complex exchange of signals responsible for nodulation through genome assembly, mutational, and expression analysis, and proteome characterization of legumes (e.g., Sato et al, 2008; Young et al, 2011; Marx et al, 2016) and rhizobia (e.g., Giraud et al, 2007; Tolin et al, 2013; Čuklina et al, 2016; Remigi et al, 2016). In a previous study (Squartini et al, 2002), we described a novel species, R. sullae , that specifically induces symbiotic nodulation in the legume sulla ( Hedysarum coronarium L. syn.…”
Section: Introductionmentioning
confidence: 99%
“…The prominent feature of this group of bacteria is their molecular dialogue with plant hosts, an interaction that is enabled by the presence of a series of symbiotic genes encoding for the synthesis and export of signals triggering organogenetic and physiological responses in the plant (Spaink et al, 1987; Long, 2001). In recent years, significant progress has been made in resolving the complex exchange of signals responsible for nodulation through genome assembly, mutational, and expression analysis, and proteome characterization of legumes (e.g., Sato et al, 2008; Young et al, 2011; Marx et al, 2016) and rhizobia (e.g., Giraud et al, 2007; Tolin et al, 2013; Čuklina et al, 2016; Remigi et al, 2016). In a previous study (Squartini et al, 2002), we described a novel species, R. sullae , that specifically induces symbiotic nodulation in the legume sulla ( Hedysarum coronarium L. syn.…”
Section: Introductionmentioning
confidence: 99%
“…The repertoire of luteolin-regulated genes in E. meliloti was identified by a combination of computational predictions (e.g. sequence homologies together with structural conservation analyses) and experimental approaches Peck et al 2006;Peck et al 2013;Roux et al 2014;Schluter et al 2013;Tolin et al 2013). Genes differentially expressed in response to the plant luteolin, as well as those related to the various stages of the symbiotic interaction, were identified (Ampe et al 2003;Barnett et al 2004;Becker et al 2014;Roux et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the NodD regulon, comprising luteolin-inducible and NodDdependent genes (Barnett et al 2004;Capela et al 2005), showed that the biosynthesis of NFs is one of the major pathways induced by the luteolin, but not the only one. Indeed, other additional genes are induced by the perception of plant flavonoid signals or show in their promoter region putative binding sites for NodD besides those related to NF biosynthesis (Batista and Hungria 2012;Galardini et al 2011;Lang et al 2008;Guerreiro et al 1997;Tolin et al 2013). Similarly to other plant flavonoids, luteolin was found to induce in E. meliloti, in addition to nod genes, the expression of genes encoding the EmrAB efflux pump, the GroES and GroEL chaperonins, as well as the SyrM transcriptional regulator and three hypothetical proteins (Capela et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The prominent feature of this group of bacteria is their molecular dialog with plant hosts, an interaction that is enabled by the presence of a series of symbiotic genes encoding for the synthesis and export of signals triggering organogenetic and physiological responses in the plant [17,18]. In recent years, significant progress has been made in resolving the complex exchange of signals responsible for nodulation through genome assembly, mutational and expression analysis, and proteome characterization of legumes [14,19,20] and rhizobia [15,[21][22][23].…”
Section: Genetics and Functional Genomics Of Legume Nodulationmentioning
confidence: 99%